2003
DOI: 10.1046/j.1460-9592.2003.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐Converting Enzyme and Endothelial Nitric Oxide Synthase Polymorphisms in Patients with Atrial Fibrillation

Abstract: Experimental studies have shown a significant increase in angiotensin-converting enzyme (ACE) expression in atrial tissue of AF patients. ACE regulates the synthesis of endothelial nitric oxide (NO), which modulates autonomic nervous activity involved in the development of AF. The aim of the study was to evaluate the prevalence of ACE insertion/deletion and endothelial NO synthase (eNOS) T-786C, G894T, and 4a/4b polymorphisms in 148 patients with persistent AF, compared with 210 control subjects. ACE insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 20 publications
(19 reference statements)
4
33
1
3
Order By: Relevance
“…The clinical data suggest that the use of ACEIs and/or ARBs may be useful for delaying progression of atrial fibrosis and AF. Furthermore, there is now evidence linking polymorphisms in RAS-related genes, such as those encoding ACE and ACE2, with an increased risk of subsequent AF development, further supporting the role of RAS in AF development [83,84,88] .…”
Section: Rasmentioning
confidence: 96%
“…The clinical data suggest that the use of ACEIs and/or ARBs may be useful for delaying progression of atrial fibrosis and AF. Furthermore, there is now evidence linking polymorphisms in RAS-related genes, such as those encoding ACE and ACE2, with an increased risk of subsequent AF development, further supporting the role of RAS in AF development [83,84,88] .…”
Section: Rasmentioning
confidence: 96%
“…In the Framingham Heart Study, increased left atrial size, decreased LV fractional shortening, and higher LV wall thicknesses were independent echocardiographic predictors of AF [1]. Patients with renin-angiotensin-aldosterone system (RAAS) gene variations or polymorphisms may also be more likely to develop AF [12,13].…”
Section: Risk Factors For New-onset Afmentioning
confidence: 99%
“…Those with AF have decreased angiotensin II type 1 and increased angiotensin type 2 receptor density in the atria [19], and ACE expression is increased threefold in the atrial tissue of patients with chronic AF [20]. The DD genotype of the ACE gene may play a role in predisposition to AF [12]. A genetic study in 250 Chinese patients and 250 controls suggested that patients with RAAS gene polymorphisms (angiotensinogen gene haplotypes M235, G-6, and G-217) may be more likely to develop nonfamilial structural AF in the context of elevated atrial pressure [13].…”
Section: Ace Inhibitors and Arbsmentioning
confidence: 99%
“…[28][29][30] Furthermore, angiotensin II itself may have prothrombotic properties that might contribute to the prothrombotic tendency in AF, that is thought to add to the stroke risk of this arrhythmia. 31 Blockade of the renin-angiotensin system and AF Given the potential role for the RAAS in AF, it would be rational to suspect that RAAS blockade by ACE inhibitors and ARBs may have beneficial effects in AF.…”
Section: Other Factors Linking the Raas To Afmentioning
confidence: 99%